Предмет: Алгебра,
автор: supermma2018
решение системы уравнений 2x-y=-1 -4x+3y=-3
Ответы
Автор ответа:
0
2x=y-1. -2*(y-1)+3y= -3; -2y+2+3y= -3; -2y+3y= -3-2; y= -5. 2x= -5-1, 2x= -6, x=(-6)/2= -3. Ответ:(-3:-5).
Автор ответа:
0
y=2x+1
-4x+3(2x+1)=-3
-4x+6x+3=-3
2x=-3-3
2x=-6
x=-6/2
x=-3
y=2*(-3)+1=-6+1=-5
(-3:-5)
-4x+3(2x+1)=-3
-4x+6x+3=-3
2x=-3-3
2x=-6
x=-6/2
x=-3
y=2*(-3)+1=-6+1=-5
(-3:-5)
Похожие вопросы
Предмет: Математика,
автор: inzukurman
Предмет: Физика,
автор: victoria7740
Предмет: Алгебра,
автор: dima3petrov
Предмет: Обществознание,
автор: Vanya9560